Investigation of the interaction of levofloxacin hemihydrate with surfactants in the occurrence of salts: Conductivity and cloud point measurement - Ahsan, Sk.Md. Ali; Molla, Mohammad Robel; Rahman, Mohammad Saidur; Hossain, Md. Farhad; Wabaidur, Saikh Mohammad; Hoque, Md. Anamul; Rub, Malik Abdul; Khan, Mohammed Abdullah (Elsevier, 2019)
Conductometric and cloud point (CP) measurement techniques have been employed in order to investigate the interaction of antibiotic drug levofloxacin hemihydrate (LFH) with anionic surfactant, sodium dodecyl sulfate (SDS) as well as a non-ionic surfactant Tween-80 (Tw-80; polyethylene sorbitol ester) in the absence/occurrence of various salts over the temperature range 298.15–318.15 K keeping regular interval of 5 K. Two clear c* values were extracted for pure SDS along with (SDS + LFH) mixtures where the increase and decrease of c* values due to the addition of LFH and salts respectively demonstrated the happened interaction among the studied components where salts provided a convenient environment for aggregation of surfactants. Negative ∆G°m values of SDS in H2O/(SDS + LFH) mixtures revealed the spontaneous assembling of surfactant molecules and the stability of the aggregates. The values of ∆H°m and ∆S°m indicate the existence of hydrophobic & electrostatic interactions between drug (LFH) and surfactant (SDS). Enthalpy and entropy contributions on the standard free energy of micellization were also calculated. The CP magnitudes of Tween-80 were reduced with increasing its concentration. The occurrence of LFH/(LFH + salts) boosted to lessening the CP values. The positive ∆G°c values suggested the non-spontaneity of clouding while the obtained ∆H°c and ∆S°c values of this CP study demonstrated the two significant accelerating impacts (electrostatic/hydrophobic interactions) between LFH & Tw-80. The thermodynamic properties of transfer for both techniques were also evaluated and analyzed in detail in the current study.